Exploration of cold signalling related to ascorbate and salicylic acid in Arabidopsis thaliana - Majláth, Imre; Szalai, Gabriella; Janda, Tibor (Acta Biologica Szegediensis, 2011)
TLow temperature is a significant limiting factor on plant development in the temperate zones. We tried to explore certain steps of the cold-signalling focused on salicylic acid (SA) and ascorbic acid (AA) using Arabidopsis thaliana as a model. The results of the freezing survival tests showed that both the wild type and mutant plants had better freezing tolerance after cold hardening treatment. SA deficient plants showed a higher survival rate. Two of the polyamines, putrescine and spermine showed only significant changes under the cold hardening. Significant differences were found in the bound SA level between the temperature treatments, but it did not correlate with the AA level and the survival rates.